2017
DOI: 10.22159/ajpcr.2017.v10i11.20504
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of Chenopodium Murale (Family: Chenopodiaceae) Cultivated in Iraq, Isolation and Identification of Scopoletin and Gallic Acid

Abstract: Objective: The aim of our study was to investigate chemical constituents of leaves of Chenopodium murale since no phytochemical investigation had been done previously in Iraq.Methods: Leaves of C. murale were macerated in absolute methanol for 2 days and fractionated by petroleum ether, chloroform, ethyl acetate, and n-butanol. The ethyl acetate fraction was analyzed by high-performance liquid chromatography (HPLC) and high-performance thin-layer chromatography (HPTLC) for its phenolic acid and coumarins conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The highest phenolic compound was determined in Urtica dioica L.(0.811 mMGAE/g), and the lowest phenolic compound was found in Rumex scutatus L. (0.481 mMGAE/g). Our findings were similar to the findings of other researchers for Chenopodium album L. (Ahmed et al, 2017, Gohar et al, 2000. An other study, the highest phenolic contents were found in a Rumex scutatus L. ethanol extracts (Isbilir, 2008).…”
Section: Figure 2 Standard Graphic Prepared With Gallic Acid For Totsupporting
confidence: 93%
See 1 more Smart Citation
“…The highest phenolic compound was determined in Urtica dioica L.(0.811 mMGAE/g), and the lowest phenolic compound was found in Rumex scutatus L. (0.481 mMGAE/g). Our findings were similar to the findings of other researchers for Chenopodium album L. (Ahmed et al, 2017, Gohar et al, 2000. An other study, the highest phenolic contents were found in a Rumex scutatus L. ethanol extracts (Isbilir, 2008).…”
Section: Figure 2 Standard Graphic Prepared With Gallic Acid For Totsupporting
confidence: 93%
“…Besides the use of the leaves, young sprouts, and the seeds of Chenopodium album L. as food, Chenopodium species have also received attention because of their suggested effects in the folk medicine, including their use as an anthelmintic, stomachic, antispasmodic, diaphoretic, emmenagogue, and abortifacient traditional remedy. They are also assumed to provide relief against menstrual pain, amenorrhea, asthma, catarrh, and migraine (Ahmed et al,2017).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have always been a preferred choice of all as it plays a great role in discovering new medicines. During extraction, solvents diffuse into the solid plant material and solubilize compounds with similar polarity [8].…”
Section: Resultsmentioning
confidence: 99%
“…Source of Scopoletin: Scopoletin (7-hydroxy-6methoxy coumarin) is a phenolic coumarin isolated from various parts of the plant (roots, fruits, leaves, stems, etc.) such as Acer saccharum Marsh 45 , Aegle marmelos 30 , Aleurites moluccana (L.) 46 , Arabidopsis thaliana 47 , Artemisia annua 48 , Artemisia feddei 49 , Artemisia iwayomogi 50 , Brunfelsia hopeana 51 , Canscora decussate 52 , Chenopodium murale 53 , Cirsium setidens 54 , Clausena excavate Burm.f. (Pyin-daw-thein) 55 , Convolvulus prostrates 56 , Erycibe obtusifolia Benth 9 , Fagraea ceilanica 57 , Gossypium hirsutum 58 , Hevea brasiliensis 59 , Hedyotis capitellata 60 , Helianthus anuus 61 , Helichrysum italicum 62 , Hymenodictyon floribundum 63 , Hymenodictyon obovatum 64 , Hypochaeris radicata 65 , Ipomoea batatas 66 , Ipomoea digitata 67 , Ipomoea reniformis 68 , Lasianthus lucidus Blume1, Macaranga gigantifolia Merr 69 , Magnolia fargesii 70 , Manihot esculenta 71 , Melia azedarach L. 20 , Morinda citrifolia 12 , Morus alba L. (Po-sa) 72 , Nicotiana tabacum 73 , Scaphopetalum thonneri 74 , Sinomonium acutum 29 , Solanum lyratum 39 , Tetrapleura tetraptera 75 , Tilia cordata Mill 76 , Ulmus pumila, Ulmus campestris 77 , Viburnum tinus 7...…”
Section: Fig 1: Chemical Structure Of Scopoletinmentioning
confidence: 99%